2009
DOI: 10.1128/aem.00412-09
|View full text |Cite
|
Sign up to set email alerts
|

Relative Diversity and Community Structure of Ciliates in Stream Biofilms According to Molecular and Microscopy Methods

Abstract: Ciliates are an important component of aquatic ecosystems, acting as predators of bacteria and protozoa and providing nutrition for organisms at higher trophic levels. Understanding of the diversity and ecological role of ciliates in stream biofilms is limited, however. Ciliate diversity in biofilm samples from four streams subject to different impacts by human activity was assessed using microscopy and terminal restriction fragment length polymorphism (T-RFLP) analysis of 18S rRNA sequences. Analysis of 3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…Adopting a similar approach, Stein et al (2010) analysed the fauna and bacteria within groundwater aquifers revealing that both communities responded to the environmental impacts occurring on the surface of the land. Similar to bacterial communities, only limited evidence has so far been provided to support the possibility that communities of ciliated protozoa have the potential to provide viable assessments of freshwater ecological health (Dopheide et al 2009). Indeed, prior to Dopheide et al (2008), research in this field was significantly hampered by a lack of knowledge regarding the appropriate ciliate-specific PCR primers with which to characterise the structure and composition of these diverse microbial communities.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Adopting a similar approach, Stein et al (2010) analysed the fauna and bacteria within groundwater aquifers revealing that both communities responded to the environmental impacts occurring on the surface of the land. Similar to bacterial communities, only limited evidence has so far been provided to support the possibility that communities of ciliated protozoa have the potential to provide viable assessments of freshwater ecological health (Dopheide et al 2009). Indeed, prior to Dopheide et al (2008), research in this field was significantly hampered by a lack of knowledge regarding the appropriate ciliate-specific PCR primers with which to characterise the structure and composition of these diverse microbial communities.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, the analysis of microbial communities may provide a useful alternative measure of ecosystem health since (1) microorganisms are ubiquitous and require little sampling effort, (2) there is minimal site disturbance associated with collecting small volumes of sediment, biofilm or water for microbial community analysis, (3) the rapid life cycle of microorganisms means they may be rapid indicators of environmental change and (4) numerous methods are now available with which to characterise the genetic diversity of aquatic microbial communities using rapid community DNA fingerprinting techniques such as denaturing gradient gel electrophoresis (DGGE; Lyautey et al 2003), terminal restriction fragment length polymorphism (T-RFLP; Dopheide et al 2009) and automated ribosomal intergenic spacer analysis (ARISA; Jones et al 2007). For example, Lear et al (2009a) recently used ARISA to characterise bacterial communities within stream biofilms and identified that these communities could provide a more sensitive indicator of ecological health than macroinvertebrates within highly impacted streams.…”
Section: Introductionmentioning
confidence: 99%
“…It is more common that microbial communities change in their taxonomic composition with human impacts, which has been consistently documented in scientific literature (e.g. Cody et al 2000, Dorigo et al 2002, Cousins et al 2003, Duarte et al 2004, Duong et al 2007, Borin et al 2009, Dopheide et al 2009). We also found that the community composition of eukaryotic microbes in vernal pools was related to the percent of each subwatershed that was urban area.…”
Section: Discussionmentioning
confidence: 87%
“…Urbanization may be increasing habitat heterogeneity in vernal pools, in both space and time, resulting in higher levels of diversity. Studies of stream bacterial (Cody et al 2000) and ciliate (Dopheide et al 2009) communities also found higher richness and diversity at sites more impacted by human activity. It is plausible that in urbanized watersheds, increased nutrient runoff and changes in water chemistry following storm events create greater temporal heterogeneity in aquatic habitats, leading to increases in overall microbial diversity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation